Thermodynamics for engineers - Potter, Merle C. (McRaw-Hill, 1993)
If you want top grades and an excellent understanding of thermodynamics, this powerful study tool is the best tutor you can have! It takes you step by step through the subject, giving you lots of example problems with fully worked solutions. You also get hundreds of additional problems to solve on your own, working at your own speed. This SchaumOs Outline of Thermodynamics for Engineers gives you clear explanations of theory, as well as numerous examples of practical applications. And the fully solved problems show you just how to work the kinds of questions youOll face on exams!